HIV/AIDS-Related Knowledge, Attitudes and Sexual Behaviors as Predictors of Condom Use Among Young Adults in Croatia - Štulhofer, Aleksandar (Array, 2007)
Context: Although Croatia is still in an early stage of HIV infection, the rising rates of infection in other central and eastern European countries suggest the need to understand HIV knowledge, attitudes and sexual behaviors among young adults in Croatia. Methods: Data from a multistage probability sample of 1, 093 Croatians aged 18– 24 surveyed in 2005 were used in regression models that examined the associations between HIV-related knowledge, attitudes and sexual behavior and predictors of condom use at first and last sexual intercourse and condom use consistency. Results: For both men and women, condom use at first intercourse and positive attitudes toward condom use were the most robust predictors of condom use at last intercourse and consistent condom use. In addition, for women, having peers with less traditional attitudes regarding sexuality was associated with consistent condom use (odds ratio, 1.3). Conclusions: Risky sexual behaviors are common among young adults in Croatia. Pragmatic and comprehensive sex education programs should target young people before they become sexually active.